THE USE OF CAPTURED IMAGES BY REMOTELY PILOTED AIRCRAFT (RPA) IN MEASURING THE STACKED LOG VOLUME IN A STOCKYARD - Heraki, Leonardo; Lopes, Eduardo Silva; Oliveira Filho, Paulo Costa (Floresta, 2022)
Quantifying wood in industrial yards quickly, accurately and at low costs is of great importance for stock management and decision making. In this work, the volume of wood logs stacked in an industrial yard was quantified using aerial images with high spatial resolution obtained by remotely piloted aircraft (RPA). The volumetric measurements were tested using the Structure from Motion with Multi-View Stereo (SfM-MVS) photogrammetry technique and compared with values obtained through the conventional manual measurement method. The aerial images were taken at three different flight heights of 60, 80 and 100 m installed at 10 ground control points using a GNSS RTK receptor. The aerial images were processed by digital photogrammetry software to generate digital surface models (DSM), which made it possible to obtain the volumetric measurements of the stacked wood. Thus, aerial images acquired at 60, 80 and 100 m altitude presented variations of 17.50%, 14.93% and 8.31%, respectively. After the statistical tests applied to the results of volumetric estimates, the SfM-MVS photogrammetry did not show significant differences for the conventional measurement method, indicating that the use of aerial images acquired by RPA can be a viable option to estimate the stacked wood volume in an industrial yard.